2015
DOI: 10.1016/j.devcel.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Proteostatic Hotspots in Amyloid Fibrils Protect Us from Neurodegeneration

Abstract: Alzheimer's disease remains a formidable challenge for therapeutic management. In a recent report in Nature Structural and Molecular Biology, Cohen et al. (2015) present intriguing results showing that "designer" molecular chaperones may hold the key to an evolutionarily conserved program for management of toxic oligomer species contributing to brain pathobiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Extracellular apolipoprotein J (Clusterin) is another chaperone found to co-localize with amyloid plaques in AD (Calero, et al, 2000) and has been shown to reduce Aβ aggregation and cytotoxicity in vitro (Yerbury, et al, 2007). Another protein domain suggested to function as a molecular chaperone and have anti-amyloid activity is the BRICHOS domain (Arosio, et al, 2016,Cohen, et al, 2015,Johansson, et al, 2006,Knight, et al, 2013,Sanchez-Pulido, et al, 2002,Singh and Balch, 2015,Willander, et al, 2011 found in the amyloid disease causing proproteins Bri2 (Sipe, et al, 2014,Vidal, et al, 1999,Vidal, et al, 2000 and proSP-C (Sipe, et al, 2014,H. Willander, et al, 2012a.…”
Section: The Complexity Of Protein Folding and How It Is Modulated Bymentioning
confidence: 99%
“…Extracellular apolipoprotein J (Clusterin) is another chaperone found to co-localize with amyloid plaques in AD (Calero, et al, 2000) and has been shown to reduce Aβ aggregation and cytotoxicity in vitro (Yerbury, et al, 2007). Another protein domain suggested to function as a molecular chaperone and have anti-amyloid activity is the BRICHOS domain (Arosio, et al, 2016,Cohen, et al, 2015,Johansson, et al, 2006,Knight, et al, 2013,Sanchez-Pulido, et al, 2002,Singh and Balch, 2015,Willander, et al, 2011 found in the amyloid disease causing proproteins Bri2 (Sipe, et al, 2014,Vidal, et al, 1999,Vidal, et al, 2000 and proSP-C (Sipe, et al, 2014,H. Willander, et al, 2012a.…”
Section: The Complexity Of Protein Folding and How It Is Modulated Bymentioning
confidence: 99%
“…In addition, the mixture shows potent general molecular chaperone activity, measured as ability to prevent non-fibrillar aggregation of destabilized model substrate proteins 28 . The nature of the secondary nucleation sites is unknown and further studies of BRICHOS effects on Aβ42 fibrillization may provide valuable information on the way in which the secondary pathway functions 30 .…”
Section: Introductionmentioning
confidence: 99%
“…The BRICHOS domain binds to the fibrils and efficiently blocks the sites for secondary nucleation, leading to a significant decrease in the formation of toxic oligomers during Aβ42 aggregation (Fig. ) .…”
Section: Admentioning
confidence: 99%